The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1088/0268-1242/16/7/305
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of zero-bias resistance-area product and quantum efficiency on perimeter-to-area ratio in a variable-area diode array

Abstract: The dependence of the zero-bias resistance-area (RA) product and the quantum efficiency (η) of variable-area diode arrays is numerically calculated by solving the diffusion equation in a cylindrical, three-dimensional geometry in the thick base approximation. The calculation is done for long-wavelength IR HgCdTe n + -on-p diffusion-limited photodiodes at 77 K. The inverse resistance-area product 1/(RA) and the square root of the quantum efficiency, η 1/2 , are plotted against the perimeter-to-area (P /A) ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Other studies have shown is dependent on junction depth, surface recombination velocity and the absorption coefficient, as well as on the minority carrier diffusion length ; therefore, should only be treated as a phenomenological fitting factor that represents an effective diffusion length. [10] [11] Judging by the fit qualities of the measurements in these experiments referred to, (1) appears to be a valid means of assessing the optical response of these detectors even as was expected to decrease below the absorber length with increasing proton fluence . Both optical and electrical characterization results for several of the PECs presented in this work were compared to that of companion FPAs and there was strong agreement between those results.…”
Section: Experimental Routinesmentioning
confidence: 93%
See 2 more Smart Citations
“…Other studies have shown is dependent on junction depth, surface recombination velocity and the absorption coefficient, as well as on the minority carrier diffusion length ; therefore, should only be treated as a phenomenological fitting factor that represents an effective diffusion length. [10] [11] Judging by the fit qualities of the measurements in these experiments referred to, (1) appears to be a valid means of assessing the optical response of these detectors even as was expected to decrease below the absorber length with increasing proton fluence . Both optical and electrical characterization results for several of the PECs presented in this work were compared to that of companion FPAs and there was strong agreement between those results.…”
Section: Experimental Routinesmentioning
confidence: 93%
“…[17] [18] would now have a -dependence since a linear increase in with increasing is still expected. Formally, damage factor analysis typically only considers linear changes with and thus, formally-speaking, it is that should be examined for , where related to by (10) of a non-ideal nBn is considered next. If a depletion region of width exists in the detector's narrow gap layer, due either to the detector's design or from operating at a slightly higher than intended reverse bias voltage, then a generation-limited dark current density component , given by (11) will also be present.…”
Section: Whenmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantum efficiency η and R 0 A product (R 0 -differential resistance at 0 bias voltage; Adiode area) was numerical calculated for p-P MCT HES taking into account only diffusion current in which the lateral diffusion current contribution becomes essential [21,22]. The diffusion current is determined from decision of stationary continuity equation for excess electron in р range.…”
Section: Mct Hes P-p Designmentioning
confidence: 99%
“…On the right side we extract the effective sidewall resistivity, q Surface , and bulk-limited dynamic impedance-area product (R eff A) Bulk by fitting the dependence of (R eff A) À1 on the perimeter-to-area ratio (P/A) for a series of diodes with diameters varying from 100 to 400 lm, as described in Ref. [16]:…”
Section: Shallow Etch Mesa Isolation (Semi)mentioning
confidence: 99%